In Vivo Pathogenecity Study Of Inclusion Body Hepatitis (Ibh) Virus In Experimentally Infected Broiler Chicks And Chickens - Thakor, K.B.; Dave, C.J.; Dave, C.J.; Fefar, D.T.; Chauhan, P.M.; Kapadiya , F.M. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
Inclusion body hepatitis (IBH) virus primarily affects the broiler birds between the ages of 3 and 5 weeks under field conditions. This investigation was planned to study the pathogenicity of IBH virus by infecting broilers through intramuscular route using liver homogenate of IBH affected birds. Total 20 birds of two age groups were selected for the in vivo study, which included day-old broiler chicks (n=10, Group A) and twenty days old chickens (n=10, Group B). In both Group A and B, five birds each were inoculated with 0.2 ml infected liver homogenate suspension by i/m route, i.e. treatment groups (T) and remaining five birds injected i/m with 0.2 ml normal saline served as control groups (C). All birds were kept under observation for five days to record morbidity and mortality. In infected/treated chicks of Group A, 100% mortality was observed on third day, while in infected/ treated chickens of Group B only 40% mortality was recorded within five days of observation period. Clinical signs like reduced feed intake and depressed appearance were observed in both the in vivo infected groups. However, hydropericardium syndrome was observed in infected birds of only Group B. Eosinophilic intranuclear inclusion bodies were observed in the hepatic cells of both the infected groups, which confirmed the disease as inclusion body hepatitis. The results indicated that the 0.2 ml liver homogenate of IBH affected birds was more pathogenic in day-old chicks than the older ones due to age factor.
Keywords: Broiler Chick; Chicken; Hydropericardium; IBH; In vivo Pathogenicity